Characterization of the Novel Protein KIAA0564 (Von Willebrand Domain-Containing Protein 8) - Luo, Moulun (Biochem Biophys Res Commun, 2017)
The VWA8 gene was first identified by the Kazusa cDNA project and named KIAA0564. Based on the observation, by similarity, that the protein encoded by KIAA0564 contains a Von Willebrand Factor 8 domain, KIAA0564 was named Von Willebrand Domain-containing Protein 8 (VWA8). The function of VWA8 protein is almost unknown. The purpose of this study was to characterize the tissue distribution, cellular location, and function of VWA8. In mice VWA8 protein was mostly distributed in liver, kidney, heart, pancreas and skeletal muscle, and is present as a long isoform and a shorter splice variant (VWA8a and VWA8b). VWA8 protein and mRNA were elevated in mouse liver in response to high fat feeding. Sequence analysis suggests that VWA8 has a mitochondrial targeting sequence and domains responsible for ATPase activity. VWA8 protein was targeted exclusively to mitochondria in mouse AML12 liver cells, and this was prevented by deletion of the targeting sequence. Moreover, the VWA8 short isoform overexpressed in insect cells using a baculovirus construct had in vitro ATPase activity. Deletion of the Walker A motif or Walker B motif in VWA8 mostly blocked ATPase activity, suggesting Walker A motif or Walker B motif are essential to the ATPase activity of VWA8. Finally, homology modeling suggested that VWA8 may have a structure most confidently similar to dynein motor proteins.